Efficiency Analysis of Pharmaceutical Companies in Pakistan: A Case Study of Ten Famous Companies - Riaz, Madiha; Kazmi, Syed Mumtaz Ali; Iqbal, Muhammad Shahid; Hussain, Altaf (Pakistan Journal of Humanities and Social Sciences, 2023)
Pharmaceutical companies contribute a remarkable amount to the Gross Domestic Product (GDP), employment, and poverty reduction. Pakistan has a very dynamic and reforming Pharmaceutical Industry. Around 759 pharmaceutical companies are operating in Pakistan. However, the study selected 10 leading pharmaceutical companies as a sample. Data Envelopment Analysis (DEA) was applied to analyse the efficiency of Pharmaceutical companies in selecting Total Assets, Liabilities, Equity, Salaries, Wages and other benefits, Sales, Earning Per Share (EPS), Dividend Per Share (DPS), and Return on Equity (ROE). The study ranked the pharmaceutical companies about the optimum utilization of input resources and to maximize the output that provides a guideline to other pharmaceutical companies to increase their revenues by improving their resource utilization following the leading companies’ models. Moreover, adopting the same strategy in figuring out ways to increase their efficiencies. This increase in efficiency will make the entire industry better off. It will also increase the GDP of the country.